When perfectionism becomes willpower - Daniele Pennesi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2016)
Perfectionism can be healthy: striving for perfection requires the ability to selfregulate, namely willpower. This paper formalizes the intuitive relation between healthy perfectionism and willpower in the presence of temptation. The value of a menu of options for an individual with limited willpower corresponds to the lower bound of the value assigned to the same menu by a perfectionist, when temptation and perfectionism intensities are free to vary. Moreover, the higher the perfectionism strive, the higher the willpower. The relation between overwhelming temptation and the Strotz model is a particular case of the result. When there is uncertainty about temptation, we generalize Dekel and Lipman (2012) providing conditions such that a preference is represented by a random willpower representation, if and only if, it has an equivalent random perfectionism representation.
Keywords: D01; 330